The profession of research management and administration in Finland - Backman Jaana; Haverinen Soile; Bingham Ella (Emerald Group Publishing Ltd., 2025)
Finland aims to increase its research and development (R&D) expenditure to 4% of gross domestic product (GDP) by 2030. The parliamentary working group proposed to advance Finland's research, development and innovation objectives which are now strongly committed by the Finnish government. This will allow universities to invest in the research and innovation not only more in the future but also in the long-term and sustainable way.
This would also provide opportunities and challenge the national research management and administration (RMA) community to develop the RMA profession, not only to increase the number of RMAs, but also to better meet the more diverse and complex tasks of the future RMA profession. Finn-ARMA creates a good platform for co-operation between RMAs in various positions and for the professionalisation of the current community and its future new members.
The Emerald Handbook of Research Management and Administration Around the World